Qualitative and quantitative analysis of the bioactive components of “ginseng–polygala” drug pair against PC12 cell injury based on UHPLC-QTOF-MS and HPLC - Wang, Zhengyang; Sun, Xiaomeng; Zhao, Yue; Ga, Liba; Li, Qi; Li, Qian; Wang, Xiaotong; Yang, Chunjuan (Frontiers in Pharmacology, 2022)
Aβ25-35 induced PC12 cells were used as the in vitro injury model to evaluate the effects on PC12 cells after intervention with “ginseng-polygala” drug pair. The results showed that the drug pair could significantly increase cell activity, reduce the level of reactive oxygen species and the concentration of inflammatory factors. Furthermore, to rapidly identify and classify complicated bioactive components of the drug pair, a liquid chromatography with quadrupole time-of-flight mass spectrometry method combined with multiple data-processing approaches was established. With this strategy, 40 constituents were preliminarily identified and the compounds database was successfully established. Among them, 12 compounds of different categories were accurately identified by comparison with reference substances. The content of the above active components was simultaneously determined by HPLC to control the quality of compatible medicinal materials, and the verification results of the analytical method met the content determination requirements. The results revealed that after the compatibility, the content change of the components is not the simple addition of quantity, but the comprehensive effect of the two medicines. In conclusion, this study could provide a generally applicable strategy for the pharmacological activity, structural identification and content determination in traditional Chinese medicine and its compatibility.